A combined scheme of edge-based and node-based smoothed finite element methods for Reissner–Mindlin flat shells. (April 2016) - Nguyen-Hoang, Son; Phung-Van, Phuc; Natarajan, Sundararajan; Kim, Hyun-Gyu
Abstract In this paper, a combined scheme of edge-based smoothed finite element method (ES-FEM) and node-based smoothed finite element method (NS-FEM) for triangular Reissner–Mindlin flat shells is developed to improve the accuracy of numerical results. The present method, named edge/node-based S-FEM (ENS-FEM), uses a gradient smoothing technique over smoothing domains based on a combination of ES-FEM and NS-FEM. A discrete shear gap technique is incorporated into ENS-FEM to avoid shear-locking phenomenon in Reissner–Mindlin flat shell elements. For all practical purpose, we propose an average combination (a ENS-FEM) of ES-FEM and NS-FEM for shell structural problems. We compare numerical results obtained usinga ENS-FEM with other existing methods in the literature to show the effectiveness of the present method.